Bede rere rangeland unit seasonal grazing areas - Getahun, Yasin (International Livestock Research Institute, 2024)
Map of grazing areas of Bede rera Rangeland Unit, Oromia region, Ethiopia where participatory rangeland management (PRM) is being supported as part of a One Health approach.